2020
DOI: 10.1371/journal.pone.0230064
|View full text |Cite
|
Sign up to set email alerts
|

Serum pepsinogens as a gastric cancer and gastritis biomarker in South and Southeast Asian populations

Abstract: Serum pepsinogens have been widely acknowledged as gastric mucosal biomarkers; however, a multicountry report on the benefits of pepsinogens as biomarkers has not yet been published. We analyzed 1,206 sera and gastric mucosal samples collected from Bangladesh, Bhutan, Indonesia, Myanmar, Nepal and Thailand then assessed the association between gastric mucosal changes and Helicobacter pylori infection. The new cutoff values for serum pepsinogen values were evaluated using a receiver operating characteristic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…The serum PG can directly reflect the functional state and morphology of the gastric mucosa as well as the number of glands and cells and is an important serum marker for the diagnosis of atrophic gastritis and monitoring of early gastric cancer. [5][6][7] Some studies have shown that there are obvious differences in PG among healthy subjects in different countries and regions. It may be due to the different detection methods and reagents, the differences in the HP infection situation of the population in each region, gender, age composition and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…The serum PG can directly reflect the functional state and morphology of the gastric mucosa as well as the number of glands and cells and is an important serum marker for the diagnosis of atrophic gastritis and monitoring of early gastric cancer. [5][6][7] Some studies have shown that there are obvious differences in PG among healthy subjects in different countries and regions. It may be due to the different detection methods and reagents, the differences in the HP infection situation of the population in each region, gender, age composition and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…PG is a pepsin precursor that secreted by the main cells of the gastric mucosa, and can be transformed into active pepsin through hydrochloric acid and activated pepsin in the stomach. PGI and PGII are the main members of the PG family (14). PG is almost exclusively secreted by the stomach, and the secretion amount will also change during the secretion stage.…”
Section: Discussionmentioning
confidence: 99%
“…Serum pepsinogen (PG) has been identified and considered the most effective non-invasive biomarker available for diagnosis of severe atrophic gastritis or gastric cancer in the community [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ]. PG can be classified immunologically into two types: pepsinogen I (PGI) and pepsinogen II (PGII) and the pepsinogen ratio (PGR: PGI/PGII) was also calculated [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…PG can be classified immunologically into two types: pepsinogen I (PGI) and pepsinogen II (PGII) and the pepsinogen ratio (PGR: PGI/PGII) was also calculated [ 11 ]. However, the use of it is still controversial [ 17 , 18 ], since it is also recommended to use with cautions [ 13 ] and its cut-off values vary from population to population [ 9 , 19 , 20 ]. Recently, the cut-off values of PGI ≤70 ng/ml and/or PGR ≤3 were widely accepted [ 12 , 21 ] while the best cut-off value for atrophy gastritis was PGI ≤50.3 ng/ml and the cut-off point for severe atrophy was PGR ≤4.28 in China [ 10 ].…”
Section: Introductionmentioning
confidence: 99%